Making Legal History : Essays in Honor of William E. Nelson - Bernstein, Richard B., 1956-; Hulsebosch, Daniel Joseph; Nelson, William E. (William Edward), 1940- (Book collections on Project MUSE., 2013)
One of the academy's leading legal historians, William E. Nelson is the Edward Weinfeld Professor of Law at New York University School of Law. For more than four decades, Nelson has produced some of the most original and creative work on American constitutional and legal history. His prize-winning books have blazed new trails for historians with their substantive arguments and the scope and depth of Nelson's exploration of primary sources. Nelson was the first legal scholar to use early American county court records as sources of legal and social history, and his work (on legal history in Engl.